A rare case of bilateral acute retinal necrosis due to varicella zoster virus in a patient of Multiple myeloma - Priyanka; Jyotirmay Biswas; Bhavana Sharma (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2017)
Introduction Clinically, ARN is characterized by anterior uveitis, vitritis, retinal necrosis beginning in the peripheral retina, and occlusive vasculitis involving the retina and choroid [1,2]. Onset is typically unilateral with visual loss, often with ocular or periocular discomfort. Sequential bilateral involvement occurs in up to one-third of cases, usually within 3 months, but may be delayed for several years. The diagnosis of ARN syndrome is based on a clinical examination and a characteristic fundoscopic appearance. Diagnostic vitrectomy or retinal biopsy may be indicated in some atypical cases. Case Report A 68-year-old male diagnosed case of Multiple myeloma, presented with gradual & progressive diminution of vision in both eye for last 6 weeks. He had received four cycle of chemotherapy before presentation. On ocular examination, visual acuity in the right eye was 6/60 and 6/36 in left eye. Intraocular pressures in both eyes were normal (10 mm Hg) by Goldman applanation tonometry. Slit lamp examination showed anterior chamber cells 1+ with vitreous cell 1+ in both eye [3]. Fundus examination revealed Vitreous haze 2+ with extensive areas of whitening and retinal necrosis involving the peripheral retina in both eye (Figures 1,2). Right eye anterior chamber tap done for Polymerase chain reaction (PCR) for herpes simplex (HSV), herpes zoster, varicella zoster (VZV), cytomegalovirus (CMV).